2010
DOI: 10.1136/bmj.c6495
|View full text |Cite
|
Sign up to set email alerts
|

Non-specific effects of standard measles vaccine at 4.5 and 9 months of age on childhood mortality: randomised controlled trial

Abstract: Objective To examine in a randomised trial whether a 25% difference in mortality exists between 4.5 months and 3 years of age for children given two standard doses of Edmonston-Zagreb measles vaccines at 4.5 and 9 months of age compared with those given one dose of measles vaccine at 9 months of age (current policy). Design Randomised controlled trial. Setting The Bandim Health Project, Guinea-Bissau, which maintains a health and demographic surveillance system in an urban area. Participants 6648 children aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
347
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(370 citation statements)
references
References 48 publications
19
347
4
Order By: Relevance
“…22,23 We recently observed that neonatal VAS followed by 3 doses of DTP and an early MV was particularly harmful for boys. 39 Thus, the combination of VAS and several vaccines may not benefit boys. In the present trial, we were not able to confirm the observation that VAS provided with DTP was particularly bad for girls, but it should be noted that at least one-third of the DTP-vaccinated children received MV during follow-up.…”
Section: Potential Interactions With Gender and Vaccinesmentioning
confidence: 99%
“…22,23 We recently observed that neonatal VAS followed by 3 doses of DTP and an early MV was particularly harmful for boys. 39 Thus, the combination of VAS and several vaccines may not benefit boys. In the present trial, we were not able to confirm the observation that VAS provided with DTP was particularly bad for girls, but it should be noted that at least one-third of the DTP-vaccinated children received MV during follow-up.…”
Section: Potential Interactions With Gender and Vaccinesmentioning
confidence: 99%
“…12 Since the HTMV was fully protective against measles, the HTMV incident provided conclusive evidence that vaccines may have unexpected negative NSE and that these NSE can be sex-differential. 21 and BCG. 33 We succeeded in testing the effect of MV by providing an additional MV at 4.5 months of age in a large randomized trial.…”
Section: Non-specific Effects Of Vaccinesmentioning
confidence: 99%
“…In addition, transferred maternal antibodies from vaccine-induced protection rather than naturally acquired measles virus infection generally result in lower geometric mean titers that wane faster, leaving the infant unprotected in early infancy [23,24]. Few published reports exist documenting increased risk of measles in younger infants due to the loss of protection in infants in low income settings and among mothers with vaccine-induced immunity [25,26], and implications of receiving MCV1 at an early age [27,28]. Information is needed to understand the role of infants in sustaining measles virus transmission in these settings, and for development of vaccination strategies to achieve elimination, particularly as exposure to wild measles virus becomes rarer.…”
Section: What Are the Causes Of Measles Outbreaks In Settings With Himentioning
confidence: 99%